Evaluasi Kinerja Mesin Kiln Berdasarkan Overall Equipment Effectiveness (OEE) sebagai Dasar Penerapan Total Productive Maintenance (TPM) di PT XYZ - Angga Bahri Pratama; Eka Putra Dairi Boangmanalu; Sahat Sahat; Jandri Fan HT Saragi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
The kiln machine demonstrates high operational effectiveness and infrequent breakdowns; however, this performance does not correlate linearly with the resulting product quality. The presence of yield losses—the discrepancy between actual specification-compliant output and total output—indicates production inefficiency, particularly regarding quality. This study aims to analyze the effectiveness of the kiln machine in activated carbon production at PT. XYZ uses the Overall Equipment Effectiveness (OEE) approach and proposes implementing Total Productive Maintenance (TPM) to minimize losses. The methodology involves measuring three primary OEE components: Availability Ratio, Performance Efficiency Ratio, and Rate of Quality Product. Analysis results reveal an average OEE value of 64.1%, which remains significantly below the Japan Institute of Plant Maintenance ideal standard of 85%. This suboptimal OEE value is primarily driven by a low Rate of Quality Product at 56.89% due to high yield losses. By implementing TPM, the company is expected to enhance kiln machine effectiveness through structured maintenance, autonomous operator maintenance, and comprehensive operational quality optimization, thereby improving overall manufacturing productivity.